Militarisation of COVID-19 responses and autocratisation: A comparative study of eight countries in Asia-Pacific and Latin America - Aurel Croissant; David Kühn; Ariam Macias-Weller; David Pion-Berlin (German Institute of Global and Area Studies (GIGA), 2023)
This paper examines the relationship between the militarisation of COVID-19 state responses and autocratisation in eight Asian and Latin American countries. Using a conceptual framework of COVID-19-related military missions and operations, our findings for each country over the first two pandemic years show that although military engagements in the COVID-19 response profiles considerably varied, all governments deployed their military, especially in the provision of health services, logistics, and the production of COVID19 goods. Meanwhile, soldiers were generally less involved in health bureaucracy and public security. Based on two rounds of an expert survey, we then evaluated whether military pandemic deployments negatively affected democratic standards. This was the case where soldiers routinely conducted public-security operations autonomous of effective civilian oversight. Our study concludes that the pandemic did not induce autocratisation; rather, it exacerbated pre-existing conditions and problems in the democratic governance of the security sector. This "acceleration effect" was visible in democracies and autocracies experiencing autocratisation already prior to the pandemic.
Keywords: 300; COVID-19; civil-military relations; militarisation; democratic backsliding; disaster response